2021
DOI: 10.3389/fcell.2021.629212
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Pancreas Development and Dysfunction Through the Lens of Single-Cell RNA-Sequencing

Abstract: A chronic inability to maintain blood glucose homeostasis leads to diabetes, which can damage multiple organs. The pancreatic islets regulate blood glucose levels through the coordinated action of islet cell-secreted hormones, with the insulin released by β-cells playing a crucial role in this process. Diabetes is caused by insufficient insulin secretion due to β-cell loss, or a pancreatic dysfunction. The restoration of a functional β-cell mass might, therefore, offer a cure. To this end, major efforts are un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 221 publications
(408 reference statements)
2
10
0
Order By: Relevance
“…5C), the dynamic profiles showed that Sox9 was active early on, confirming its role in inducing Neurog3 in the progenitor cord 65 . Additionally, we found Meis2 with an increasing profile towards the end of the β-trajectories; previous studies reported it to be enriched in the second wave of murine fetal α cells 66 , but its specific role in β-cell differentiation remains known. We observed two dynamic waves regarding the human-specific factors (Fig.…”
Section: Resultssupporting
confidence: 47%
See 1 more Smart Citation
“…5C), the dynamic profiles showed that Sox9 was active early on, confirming its role in inducing Neurog3 in the progenitor cord 65 . Additionally, we found Meis2 with an increasing profile towards the end of the β-trajectories; previous studies reported it to be enriched in the second wave of murine fetal α cells 66 , but its specific role in β-cell differentiation remains known. We observed two dynamic waves regarding the human-specific factors (Fig.…”
Section: Resultssupporting
confidence: 47%
“…Additionally, we found Meis2 with an increasing profile towards the end of the -trajectories; previous 66 , but its specific role in -cell differentiation remains known. We observed two dynamic waves regarding the human-specific factors (Fig.…”
Section: Differential Motif Activity Analysis Predicts Driving Factor...supporting
confidence: 58%
“…The Notch and canonical Wnt pathways are known to block EP specification [52][53][54][55]. Thus, Amotl2 might regulate EP specification upstream of Neurog3 [56]. AMOTL2 knockdown in human ES cell-derived CP cells increases glucagon and decreases insulin expression at the endocrine cell stage [46].…”
Section: Heterogeneity Of Endocrine Cell Developmentmentioning
confidence: 99%
“… 11 , 13 More detailed information on the use of scRNAseq to provide wider information on pancreas development may be found in a recent review. 32 …”
Section: Single‐cell Rna Sequencingmentioning
confidence: 99%
“…In addition, these studies have provided information on pseudo‐time ordering, which has led to improved understanding of the order in which genes are expressed during pancreatic cell lineage specification 11,13 . More detailed information on the use of scRNAseq to provide wider information on pancreas development may be found in a recent review 32 …”
Section: Single‐cell Rna Sequencingmentioning
confidence: 99%